Sistem Kerja Buka Tutup Pintu Secara Automatis Menggunakan Foto Sensor dan Sistem Manual Pneumatik - Hendri, Afianto; Harini, Harini; Ramzani, Rizki; Sasmito, Misadi (Marine Science and Technology Journal, 2023)
Pneumatic systems are systems that use air as a propellant and are used in todays computerized systems. The task will use a pneumatic machine to manually open and near the door with sensors and buttons. design and model fluid simulators from Festo to attain the preferred aerodynamic design. Diagram of pneumatic system consistent with its operating. System used double appearing cylinder 5/2 solenoid valve 5/3 control valve photoelectric sensor magnetic sensor push button compressor & electric powered. The tool is geared up with an electrical and passive circuit that acts as a damper piston solenoid valve that activates a photoelectric sensor to open the door and a magnetic sensor to connect the voltage to the motor. A manual gadget can be used the use of ahead and reverse buttons in case of strength failure while last the door. The results of this study display that photoelectric sensors and magnetic sensors can be used to show a button right into a switch that turns off or adds cutting-edge to an electromagnetic-type electricity source. capturing with flash is hard. It additionally has a mechanical activation characteristic thru a button that without difficulty opens and closes the door inside the event of a power failure.